Entry barriers, competition, and technology adoption - Lei Fang (Federal Reserve Bank of Atlanta, 2009)
There are large differences in income per capita across countries. Growth accounting finds that a large part of the differences comes from the differences in total factor productivity (TFP). This paper explores whether barrier to entry is an important factor for the cross-country differences in TFP. The paper develops a new model to link entry barriers and technology adoption. In the model, higher barriers to entry effectively reduce entry threat, and lower entry threat leads to adoption of less productive technologies. The paper demonstrates that technology adopted in the economy with entry threats is at least as good as the technology adopted in the economy without entry threats. Moreover, the paper presents numerical simulations that suggest entry barriers could be a quantitatively important reason for cross-country differences in TFP and are more harmful to productivity in the countries with monopolists facing inelastic demand.
Keywords: O11; O43; 330; entry barriers; technology adoption; total factor productivity